2011
DOI: 10.1159/000322825
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Successful Varicocelectomy in Infertile Patients

Abstract: Aim: To examine the predictive factors of successful varicocelectomy in infertile patients. Methods: Thirty-five infertile male patients with varicocele and requiring varicocelectomy were recruited in this study. The patients were divided into 2 groups based on their recovery outcome after subinguinal microsurgical varicocelectomy. Patients who showed significant improvement on their sperm density, motility and morphology 6 months after varicocelectomy were designated as group 1, whereas those who showed no im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
2
32
0
1
Order By: Relevance
“…() suggested that varicocele is a risk factor for androgen deficiency, and that testosterone levels may increase after varicocelectomy. Our previous study showed that the significant predictive factors of successful varicocelectomy in infertile patients with varicocele were high testicular volume, low serum concentration of FSH and high number of ligated veins (Chen & Chen, ). In this study, patients in group 1 had lower serum FSH levels, and higher testicular volume before redo varicocelectomy than those in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…() suggested that varicocele is a risk factor for androgen deficiency, and that testosterone levels may increase after varicocelectomy. Our previous study showed that the significant predictive factors of successful varicocelectomy in infertile patients with varicocele were high testicular volume, low serum concentration of FSH and high number of ligated veins (Chen & Chen, ). In this study, patients in group 1 had lower serum FSH levels, and higher testicular volume before redo varicocelectomy than those in group 2.…”
Section: Discussionmentioning
confidence: 99%
“…Shindel, et al19 found that the number of veins ligated correlated positively with an increase in total motility ( p =0.017). Chen, et al20 found that patients who showed significant improvement in their sperm density, motility and morphology 6 months after varicocelectomy had higher numbers of ligated veins (9.3±0.8 vs. 7.9±0.7) than patients who showed no improvement 6 months after surgery 20. These imply that for a higher number of ligated ISVs, there is greater improvement in semen parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Serum testosterone was measured using a radio-immuno assay (RIA) (Coat-a-Count from Diagnostic Products Corporation, Los Angeles, CA). The sensitivity of the Diagnostic Products Corporation testosterone assay was 0.23 nmol/L, and the intra- and interassay coefficients of variation were both <10% Execution of genetic assessment (karyotype, y microdeletion and cystic fibrosis screening) in the patients with a sperm concentration <5 × 10 6 /ml[ 9 10 ] Execution of surgery only on patients with 3 rd , 4 th or 5 th degree varicocele. [ 1 2 ] The varicoceles were graded as follows using Duplex scans in all centers: grade 1: venous reflux with a Valsalva maneuver limited to the cranial portion of the cord, grade 2: reflux with Valsalva until the upper pole of the testicle, grade 3: reflux with Valsalva until the lower pole of the testicle, grade 4: reflux under basal conditions increased by Valsalva and grade 5: reflux under basal conditions which did not increase with Valsalva[ 11 ] loop magnification subinguinal varicocelectomy (a microscope was never used) repetition of the initial assessment (i.e., clinical history collection, objective examination, hormonal levels, two semen analyses and scrotal duplex examination) at least 6-8 months after surgery and each time advice for (in) fertility was requested assessment of female factors of infertility before surgery and each time advice for (in) fertility was requested[ 12 ] the presence of an “expert laboratory” dedicated to sperm analyses in each center.…”
Section: Methodsmentioning
confidence: 99%